Legítima defensa en la era tecnológica: una interpretación desde la teoría de la imputación objetiva - Vaca Espinosa, Jorge Rafael (DIXI, 2025)
Self-defense is a particularly important topic in the study of criminal dogmatics and has traditionally been the subject of significant debates regarding its requirements or components. For example, aspects such as proportionality, the necessity of defense, and the immediacy of the attack have been widely discussed. While there is consensus on these elements in most cases, this doctrinal agreement becomes less clear when it comes to defensive self-defense (“legítima defensa ofendicular”), which, broadly speaking, refers to the installation of defensive mechanisms against potential attacks. An example of this would be placing shards along the edges of walls to prevent intruders from entering a property. If this issue has long been a subject of debate, the discussion becomes particularly relevant in contemporary society, where technology is an indispensable part of daily activities. In this context, new cases emerge, such as reactions to attacks conducted by unmanned aerial vehicles or drones. Therefore, this study aims to analyze the implications of the theory of objective imputation within the dogmatics of defensive self-defense and its relationship with phenomena inherent to a technologized society. This will be approached through a qualitative methodology with a legal focus, structured around the study of the normative framework of the concept of crime. As a result, the research proposes that defensive self-defense should be examined as an element of objective imputation, specifically from the perspective of the permitted risk component.